2022
DOI: 10.1001/jamahealthforum.2022.0760
|View full text |Cite
|
Sign up to set email alerts
|

Projecting COVID-19 Mortality as States Relax Nonpharmacologic Interventions

Abstract: This simulation modeling study projects COVID-19 deaths between March 1, 2022, and December 31, 2022, in each of the 50 US states, District of Columbia, and Puerto Rico assuming different dates of lifting of mask mandates and nonpharmacologic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…A systematic review by Brito and coworkers reported that some less disruptive NPIs, such as mask wearing requirements, were also effective [ 50 ]. It is worth noting, then, that while vaccinations are the most effective tool in reducing cases and deaths, NPIs can still provide a useful safety net [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Brito and coworkers reported that some less disruptive NPIs, such as mask wearing requirements, were also effective [ 50 ]. It is worth noting, then, that while vaccinations are the most effective tool in reducing cases and deaths, NPIs can still provide a useful safety net [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, all countries should adopt a vaccines-plus approach, which includes a combination of COVID-19 vaccination, other prevention measures, treatment and financial incentives such as support measures. Infection rates tend to increase when governments discontinue social measures, including non-pharmaceutical interventions, regardless of the level of vaccination 57 , 58 .…”
Section: Top-ranked Consensus Recommendationsmentioning
confidence: 99%
“…Finally, setting thresholds is complicated by the evolving relationship between epidemiologic indicators and outcomes ( 15–17 ). In the future, this evolution will continue to be driven in large part by features of new variants ( 18 ) but also by levels of increasing and decreasing immunity from infection and vaccination ( 19 ); development and delivery plans for updated vaccines ( 20 ); availability and uptake of testing and antiviral treatments ( 21 , 22 ); and changing policies and practices on preventive measures, such as masking, testing, and isolation and quarantine ( 23 ). In the context of uncertain and changing conditions, well-defined objectives are particularly important to allow efficient updating of metrics to accommodate this flux.…”
Section: Discussionmentioning
confidence: 99%